Identification of Insect Pests in Oil Palm Plantations (elaeis guineensis jacq) PT. Jamika Raya, Sekar Mengkuang Village, Limbur Lubuk Mengkuang District, Bungo Regency - Budi Prastia; Subagiono Subagiono; Agus Agus (Fakultas Pertanian Universitas Muara Bungo, 2023)
This research aims to identify pests that attack oil palm plants (Elaeis guineensis jacq) PT. Jamika Raya and want to know the level of pests that dominate oil palm plantations and their level of diversity. This research will be carried out at PT. Jamika Raya palm oil unit, whose address is Sekar Mengkuang Hamlet, Limbur Lubuk Mengkuang District. This research is planned from May to June 2022. The tools used in this research are plastic bottles or cups for capturing samples, wood, digital camera, rope, knife, magnifying glass, millimeter block, cardboard loupe and insect determination key book. The research method used is descriptive purposive sample analysis research by means of a survey. Meanwhile, a survey is a method of collecting data from a number of individuals or units systematically and following scientific procedures. Sampling was taken using fishing techniques using fill traps and hand sorting techniques in the research area. Observation variables include: a. Identification b. Diversity index (H) (Shannon-Wiener) c. Uniformity Index d. Dominance index. The results of the identification of insect pests on oil palm plantations in Sekar Limbur Hamlet, Limbur District, PT. Jamika Raya, obtained 5 orders, consisting of 8 species with a total of 1209 insects, namely: Order: Lepidoptera, Fireworm, Bagworm, Hairy Caterpillar, Order Coleoptera: Horn beetles, Order Blattodea: Termites, Order Hymenoptera: Angry ants and Order Rodentia: Rats. The dominance value of insect pests in the dominant location is still low, ranging from 0.0002 – 0.144. The diversity and uniformity of insect pests in Afd. the number of 240 individuals, 120 and 100. The fewest species are horn beetles with a number of 5 individuals, 3, for afd O the species with the fewest are rats, namely 9. In the Afd.C research plot the diversity index value is 0.67 indicating that the H value ' 1 indicates that species diversity in a transect is small or low, while a uniformity index of 0.23 indicates that the distribution of individuals between species is even because the uniformity value obtained is close to 1, also for afd.D and afd,O.